Unraveling the Interconnection Patterns Across Lung Microbiome, Respiratory Diseases, and COVID-19 - Stavropoulou, Elisavet; Kantartzi, Konstantia; Tsigalou, Christina; Konstantinidis, Theocharis; Voidarou, Chrissoula; Konstantinidis, Theodoros; Bezirtzoglou, Eugenia (Frontiers in Cellular and Infection Microbiology, 2021)
Albeit the lungs were thought to be sterile, recent scientific data reported a microbial microbiota in the lungs of healthy individuals. Apparently, new developments in technological approaches including genome sequencing methodologies contributed in the identification of the microbiota and headlight on the role of the gut and lung microbiomes in the development of respiratory diseases .Moreover, knowledge of the human microbiome in health may act as a tool for evaluating characteristic shifts in case of disease. This review paper discusses the development of respiratory disease linked to the intestinal dysbiosis which influences the lung immunity and microbiome. The gastrointestinal –lung dialogue provide interesting aspects in the pathogenesis of the respiratory diseases. Lastly, we were further interested on the role of this interconnection in the progression and physiopathology of newly emergedCOVID-19.